Hypercoagulability and Thrombosis Risk in Prostate Cancer: The Role of Thromboelastography - Fainchtein, Karina; Tera, Yousra; Kearn, Natalie; Noureldin, Abdelrahman; Othman, Maha (Seminars in Thrombosis and Hemostasis, 2022)
Thrombosis is one of the leading causes of death in cancer. Cancer-induced hypercoagulable state contributes to thrombosis and is often overlooked. Prostate cancer may not be of high thrombogenic potential compared with other cancers, but its high prevalence brings it into focus. Pathological evidence for venous thromboembolisms (VTEs) in prostate cancer exists. Factors such as age, comorbidities, and therapies increase the VTE risk further. There is a need to systematically identify the risk of VTE in regard to patient-, cancer-, and treatment-related factors to risk stratify patients for better-targeted and individualized strategies to prevent VTE. Sensitive tests to enable such risk assessment are urgently required. There is sufficient evidence for the utility of thromboelastography (TEG) in cancer, but it is not yet part of the clinic and there is only limited data on the use of TEG in prostate cancer. One study revealed that compared with age-matched controls, 68.8% of prostate cancer patients demonstrated hypercoagulable TEG parameters. The absence of clinical guidelines is a limiting factor in TEG use in the cancer population. Cancer heterogeneity and the unique cancer-specific microenvironment in each patient, as well as determining the hypercoagulable state in each patient, are added limitations. The way forward is to combine efforts to design large multicenter studies to investigate the utility and clinical effectiveness of TEG in cancer and establish longitudinal studies to understand the link between hypercoagulable state and development of thrombosis. There is also a need to study low thrombogenic cancers as well as high thrombogenic ones. Awareness among clinicians and understanding of test applicability and interpretation are needed. Finally, expert discussion is critical to identify the investigation priorities.
Keywords: coagulation; thromboelastography; thrombosis; hemostasis; prostate cancer